Effect of zirconium diboride addition on the properties of sintered Y-TZP ceramic / Kelvin Chew Wai Jin - Chew, Kelvin Wai Jin (2015)
It is well known that the high hardness of advanced ceramics such as zirconia renders the ceramics with good wear resistance but this leads to difficulty in machining as well as necessitates diamond tooling. Together with the brittle nature of ceramics, these complications result in high machining cost and prohibit the large scale manufacturing of products from advanced ceramics. An alternative machining method, the electrical discharge machining (EDM) disregards the material hardness but requires the work piece to be electrically conductive. However, most advanced ceramics such as alumina and zirconia are electrical insulators at room temperature. One possible way to reduce the resistivity of zirconia ceramic is to introduce electrically conductive phase such as zirconium diboride, ZrB2, into the zirconia matrix. The present research investigated the effects of ZrB2 content of 10, 15, 20 and 30 wt% on the mechanical properties, electrical conductivity and ageing resistance of Y-TZP ceramics. The combined materials, forming the zirconia composite were synthesized by wet ball milling method and subsequently cold isostatically pressed before sintering. Green compacts were buried in a powder bed before being pressureless sintered under argon gas condition for 2 hours at sintering temperatures of 1300°C to 1500°C. Undoped Y-TZP samples were similarly fabricated for comparison purpose. It was found that the densification of composites with 10 to 20 wt% ZrB2 content was significantly improved compared to undoped Y-TZP although the effect became less pronounced when sintered at higher sintering temperatures. No significant improvement was observed in the elastic modulus of the composites. Hardness of the ZrB2/Y-TZP composites improved with sintering temperature and the only beneficial effect of ZrB2 phase was observed for composites sintered at 1300°C. All composites showed remarkable improvement in fracture toughness compared to monolithic Y-TZP due to additional toughening mechanisms such as crack deflection, crack bridging and microcracking. In general, the ZrB2 content of up to 20 wt% did not iv affect the phase stability of tetragonal zirconia and average grain size of zirconia. There was a remarkable enhancement in electrical conductivity of the composites with higher ZrB2 content and this behaviour has been associated with the percolative effect of ZrB2 phase as evidenced by the good agreement between the experimentally data and estimates derived from the general effective media equation as well as formation of ZrB2 networks within the microstructure of the composites. In spite of the lower mechanical properties, the 30 wt% ZrB2/Y-TZP composite showed the highest electrical conductivity of 105 S/m (equivalent to resistivity of 0.001 Ω.cm) which exceeded the threshold limit of 0.01 S/m (equivalent to resistivity of 104 Ω.cm) required for EDM. In terms of ageing resistance, the research found that the undoped Y-TZP performed better than the composites. Based on the results of the present study, the 20 wt% ZrB2/Y-TZP composite was identified as the optimum composite with a good balance of mechanical properties and electrical conductivity. The experimental observations on ageing revealed that the composites underwent different ageing kinetics from undoped Y-TZP. In addition, an ageing mechanism was subsequently proposed to explain the ageing-induced tetragonal to monoclinic phase transformation observed in Y-TZP ceramic.